(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The goal of the article is to explore some linguistic means used in the British monarchical media discourse to describe the life of the Royal family. The research is carried out in the semiotic aspect with the help of contextual and distributive methods of analysis of the extensive language material taken from the authentic sources, such as: the Internet versions of British newspapers, the international news service BBC and the official website of the Windsors. The verbal signs that define the representatives of the British monarchy, their actions, relations, values and anti-values, tangible and intangible resources, quantitative characteristics, are used not only to inform the readers about the events in which the British Royals participate but also to enlarge the world picture of common citizens and to create the image of the contemporary monarchy. The results of the research show that the members of the Royal family are presented as approachable, amiable people, involved in charity, engaged in solving the urgent social issues and doing their best in popularization of monarchy, bringing it up to date. The article also contributes to the theory of discourse as it contains the definition of monarchical discourse and the characteristics of its personal, institutional and media subtypes from the point of view of their participants, the aims of the latter and the situations of communication. Key words: linguasemiotics, verbal sign, monarchical media discourse, the Royal family DOI 10.18522/1995-0640-2020-4-47-55